Exploring paramedicine student preferences using Holland's vocational theory: A cross‐sectional study. (5th August 2021) - van Huizen, Pheona; Mason, Rod; Williams, Brett
Abstract: Holland's RIASEC typology is a classification of vocational personality types and work environments. Having a predisposition for their vocation, in terms of a personality that is congruent to their work environment, may be protective for paramedics with regards to both their mental and physical health. The purpose of this study was to identify paramedicine students' vocational preference according to Holland's RIASEC model. Bachelor of Paramedicine degree students in the three different year levels completed the 48‐item Brief RIASEC Marker Scales to determine their order of the six RIASEC personality types. In this study, the paramedicine students' three most dominant personality types were Social‐Investigative‐Artistic, differing from the defined Holland Occupational Code for paramedics of Realistic‐Social‐Investigative. Male students scored significantly higher on the Reality personality type, whereas female students scored significantly higher on the Social personality type. Overall, this study found many students to possess two of the three dominant personality traits that form the desired Holland code for paramedics. This suggests that many students may be better able to cope with the demands of the paramedicine profession upon employment.